Enhanced luminescence properties and device applications of Tb3+-doped Cs4PbBr6 perovskite quantum dot glass. Issue 3 (1st February 2023) - Li, Shasha; Liu, Guanchen; Lin, Hai; Li, Chun; Zeng, Fanming; Lin, Jingquan; Xiang, Weidong
Abstract: Cs4 PbBr6 perovskite quantum dots (QDs) have unique optoelectronic properties and are expected to become a new generation of luminescent materials. However, poor stability, low photoluminescence quantum yield (PLQY), and poor understanding as to the origin of photoluminescence behavior limit its further application. In this study, a series of Tb 3+ -doped Cs4 PbBr6 perovskite QD glasses with excellent stability were obtained through the optimization of Tb 3+ doping concentration and in-situ crystallization temperature. Density functional theory calculations and experimental characterization showed that an appropriate amount of lattice-incorporated Tb 3+ ions can reduce structural defects in QDs, improve the PLQY, and reduce the QD heavy-metal requirements. Notably, the maximum PLQY value reached 47%, which is near to the Cs4 PbBr6 perovskite crystal. Furthermore, a high-performance white light-emitting diode (WLED) device was prepared. The device featured a color rendering index of 80 and luminous efficiency of 41 lm W −1 . Finally, a QD glass with double emission peaks was prepared by controlling the in-situ crystallization temperature (550 °C). The temperature sensitivity of the QD glass was then studied using the fluorescence intensity ratio method. The maximum relative temperature sensitivity (Sr) reached 2.03% K −1, which is higher than the previously reported value. Thus, the method proposed in this study can greatly improve the photoluminescence properties of Cs4 PbBr6 QD glass and expand its applications in WLED and visual temperature sensing.